Diasporic Reparations: Repairing the Social Imaginaries of Central America in the Twenty-First Century - Ana Patricia Rodríguez (Studies in 20th & 21st Century Literature, 2013)
Contemporary Central American diasporic writers like Horacio Castellanos Moya, Francisco Goldman, Héctor Tobar, and Marcos McPeek Villatoro, in Senselessness (2008), The Art of Political Murder: Who Killed the Bishop? (2007), The Tattooed Soldier (1998), and the Romilia Chacón detective series, write in response to various forms of violence. They grapple with the image of Central America as a site of unsustainable violence, inhospitable material conditions, and unresolved historical issues that extend into the lives of Central Americans in the United States. The past is not easily dismissed, but lies at the core of transnational Central American subject formation. This essay examines how violence and impunity are closely tied in Central American diasporic texts and hold cognitive relevancy for Central Americans in and outside of the isthmus. While US Central Americans seek to understand the origins and conditions of their diaspora, writers reflect critically on Central American historiography, diaspora, and the construction of transnational “Centroamericanidades” in the twenty-first century. These writers engage in a literature of reparation that reveals the (im)possibility of repairing and re-writing or righting the past in societies where violence and impunity have been institutionalized.
Keywords: diaspora; diasporic writers; Centroamericanidad; violence; impunity